Calculation of Thermal Mode of Flat Irradiated Ceramic Mass Sample’ while Evaporating Moisture from Heated-up Surface - S. N. Osipov; V. A. Bilyk (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2004)
The solution of a differential heat conduction equation is given in view of cooling effect of moisture evaporation from a heated surface. In this case heating heat flow is diminishing in time exponentially. The most typical nomographic temperature and temperature gradient charts of heated surface and mean temperature of a plate are presented in the paper.